1990
DOI: 10.1111/j.1469-8986.1990.tb02343.x
|View full text |Cite
|
Sign up to set email alerts
|

Existing and Training Induced Differences in Aerobic Fitness: Their Relationship to Physiological Response Patterns During Different Types of Stress

Abstract: Aerobic fitness has been associated with various desirable psychological and physiological characteristies. Recently, attenuation of physiological reactivity during stressful situations was added to this list, although comparison of the stress responses of sportsmen and sedentary subjects has yielded equivocal results. The present study examined cardiovascular patterns rather than single variables, and tried to clarify these matters. Tasks were used that were known to increase blood pressure through different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 73 publications
4
56
0
Order By: Relevance
“…The main finding of this study, that HRV indices of parasympathetic nervous activity are sensitive indicators of mental stress during computer work, are consistent with a number of other studies using either prolonged (Bernardi et al 2000;Miyake 1997;Pagani et al 1991) or short-term exposure to psychosocial stressors (de Geus et al 1990;Sloan et al 1991). The latter two studies suggested a withdrawal of vagal modulation of the heart during short-term stress.…”
Section: Discussionsupporting
confidence: 92%
“…The main finding of this study, that HRV indices of parasympathetic nervous activity are sensitive indicators of mental stress during computer work, are consistent with a number of other studies using either prolonged (Bernardi et al 2000;Miyake 1997;Pagani et al 1991) or short-term exposure to psychosocial stressors (de Geus et al 1990;Sloan et al 1991). The latter two studies suggested a withdrawal of vagal modulation of the heart during short-term stress.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were consistent with the results of the above mentioned studies. The HRV indices of parasympathetic nervous system activity were sensitive indicators of MWL during traffic density monitoring; this main finding was consistent with a number of other studies using either prolonged (Miyake, 1997;Bernardi et al, 2000) or short-term exposure to psychosocial stressors (De Geus et al, 1990;Sloan et al, 1991). Ryu and Myung (2005) showed a clear correlation between the difficulty of the tracking task and HRV indices.…”
Section: Discussionsupporting
confidence: 89%
“…Another hypothesis to explain the beneficial effects of exercise is the reduction of cardiovascular reactivity and/or increased recovery from stress. It is postulated that the improvement of vagal tone could attenuate cardiovascular reactivity, compensating for the increases in sympathetic cardiac influences under stress (de Geus et al, 1990;Sakakibara and Hayano, 1995). Some studies have found that fitness level is associated with smaller reactivity effects on both the heart and the vessels (van Doornen and de Geus, 1989).…”
Section: Discussionmentioning
confidence: 99%